(untitled) (Revista Española de Fisiología, 1990)
The aim of this study was to evaluate the effect of total parenteral nutrition (TPN) with 100% long-chain triglyceride (LCT) (group A) and 50/50% medium/long-chain triglyceride (MCT/LCT) (group B) fat emulsions on visceral protein synthesis in 70% hepatectomized rats. The rats were fed TPN continuously for 7 days posthepatectomy. Protein synthesis was measured in the liver and jejunal mucosa with the flooding dose method. All rats received the same caloric and nitrogen intake, without statistically significant differences. The only difference between the two groups was the proportion of MCT to LCT in the diets. Hepatic and jejunal mucosa protein synthesis were significantly higher in group B, fed 50/50% MCT/LCT. These results suggest that fat emulsions with 50/50% MCT/LCT significantly enhance visceral protein synthesis after partial hepatectomy.